A single center experience with publicly funded clinical exome sequencing for neurodevelopmental disorders or multiple congenital anomalies - Pode-Shakked, Ben; Barel, Ortal; Singer, Amihood; Regev, Miriam; Poran, Hana; Eliyahu, Aviva; Finezilber, Yael; Segev, Meirav; Berkenstadt, Michal; Yonath, Hagith; Reznik-Wolf, Haike; Gazit, Yael; et al. (Scientific reports, 2021)
Exome sequencing (ES) is an important diagnostic tool for individuals with neurodevelopmental disorders (NDD) and/or multiple congenital anomalies (MCA). However, the cost of ES limits the test's accessibility for many patients. We evaluated the yield of publicly funded clinical ES, performed at a tertiary center in Israel, over a 3-year period (2018–2020). Probands presented with (1) moderate-to-profound global developmental delay (GDD)/intellectual disability (ID); or (2) mild GDD/ID with epilepsy or congenital anomaly; and/or (3) MCA. Subjects with normal chromosomal microarray analysis who met inclusion criteria were included, totaling 280 consecutive cases. Trio ES (proband and parents) was the default option. In 252 cases (90.0%), indication of NDD was noted. Most probands were males (62.9%), and their mean age at ES submission was 9.3 years (range 1 month to 51 years). Molecular diagnosis was reached in 109 probands (38.9%), mainly due to de novo variants (91/109, 83.5%). Disease-causing variants were identified in 92 genes, 15 of which were implicated in more than a single case. Male sex, families with multiple-affected members and premature birth were significantly associated with lower ES yield ( p < 0.05). Other factors, including MCA and coexistence of epilepsy, autism spectrum disorder, microcephaly or abnormal brain magnetic resonance imaging findings, were not associated with the yield. To conclude, our findings support the utility of clinical ES in a real-world setting, as part of a publicly funded genetic workup for individuals with GDD/ID and/or MCA.